Trauma and Social Pathways to Psychosis, and Where the Two Paths Meet - Heriot-Maitland, Charles; Wykes, Til; Peters, Emmanuelle (Frontiers in Psychiatry, 2022)
The pathways from trauma—via dissociation—to psychosis have been thoroughly tested and evidenced, but what has received less attention has been the social pathways—via dissociation—to psychosis. Often social factors are more commonly linked to other influences, e.g., to appraisals and the creation of negative schema in cognitive models, or to unsupportive caregiving experiences where there is high “expressed emotion.” However, evidence is now emerging that negative social rank experiences, such as being excluded or shamed, may themselves have dissociative properties, which poses intriguing questions as to how trauma pathways and social pathways might interact. This article reviews the state of knowledge in trauma and social pathways to psychosis and then considers the potential mechanisms and the relationships between them, specifically (i) dissociation, (ii) attachment, and (iii) social rank. Recommendations are suggested for future modeling and testing of three-way interactions (dissociation × attachment × social rank) in the pathway from trauma to psychosis.